PALESTINIAN RESISTANCE IN MAHMUD DARWISH'S BITHOQOH HUWIYYAH POEM: A KINAYAH STUDY - Mellinda Raswari Jambak; Muassomah Muassomah; Alam An Shori; Nabila Nur Khonsa; Aldrian Aldrian (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2024)
This research explores indirect expression in Mahmoud Darwish's poem "Bithoqoh Huwiyyah" (With Identity Confidence) to convey the message of Palestinian resistance. The poem, a significant piece of Palestinian literature, reflects the resilience of the Palestinian people in the face of ongoing oppression and struggles for identity and autonomy. Through figurative language, Darwish communicates complex political and social themes related to Palestinian resistance, using subtle forms of expression to convey powerful messages of defiance. The study employs qualitative content analysis to examine the poem's text and identify the types of indirect expression used. The primary data consists of the poem, while secondary data includes scholarly articles on Darwish, Palestinian history, and socio-political context. Data were collected using reading and note-taking techniques, and the analysis follows a three-stage process: data reduction, presentation, and conclusion drawing. The findings reveal four distinct types of indirect expression in the poem: talwih, ta'ridh, ramz, and ima'/isyarah. These expressions convey themes of resistance through various forms, such as existential declarations, social criticism, and subtle threats. For instance, Darwish uses indirect expressions like "Take note, I am an Arab" and "I am a name without a title" to assert Palestinian identity, while phrases such as "I eat the flesh of those who oppress me" express anger and opposition to injustice. These forms of figurative language enhance the poem's impact by allowing Darwish to communicate the depth of Palestinian suffering and the enduring spirit of resistance without resorting to confrontation. The study highlights how Darwish's indirect expression transforms his poetry into a tool for cultural resilience, offering both a voice for the oppressed and a means of resistance. The research contributes to the broader understanding of literature as a powerful form of political resistance, demonstrating how poetry can subtly yet profoundly influence collective identity and social movements. By analyzing the indirect expressions in Darwish's work, this study underscores the importance of art in political discourse, offering a deeper appreciation of how literature shapes the struggle for justice and freedom.